STEM : INNOVATION IN VOCATIONAL LEARNING - Fathoni, Ahmad; Muslim, Supari; Ismayati, Euis; Rijanto, Tri; -, Munoto; Nurlaela, Lutfiyah (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
AbstractIndonesia with a population of more than 200 million people, has an obligation to produce quality human resources to be able to compete with other countries. The problem currently faced is the high level of open unemployment, especially in SMK graduates. One way to improve the quality of human resources is by providing innovation in the learning process, especially in the field of vocational learning. Learning that can be applied in vocational education is learning based on STEM (Science, Technology, Engineering, and Mathematics). The purpose of this study is to describe more deeply about STEM learning as an innovative learning process that can be applied in vocational learning. The study was conducted using the literature review method of relevant research references and results, which were continued through focus group discussions (FGD). This study obtained the results of (1) STEM learning successfully applied both abroad and domestically; (2) it can improve students' creativity and critical thinking; (3) STEM learning can be integrated with learning models such as Project Based Learning, Problem Based Learning and cooperative learning; (4) Make students more confident in their future careers; and (5) STEM learning is very suitable for use in 21st century learning, especially in the vocational field so that STEM learning can be used as a solution in improving the quality of human resources and developing 21st century skills skills and in accordance with the objectives of vocational learningÂ Keywords : STEM, Innovation, Learning, Vocational